2000
DOI: 10.1002/1099-0690(200010)2000:19<3265::aid-ejoc3265>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The Paternò-Büchi Reaction of 2-Furylmethanols

Abstract: The Paternò -Büchi reaction between 2-furylmethanol derivatives and aromatic carbonyl compounds shows good regioselectivity and high stereoselectivity. The regio-and stereoselectivity of the reaction can be explained by assuming a role of both the substituent on the 2-furylmethanol derivative and the hydroxy group in order to favor the approach

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This group proposed that hydrogen-bond interactions in the exciplex played an important role in controlling the selectivity. DAuria and coworkers also observed a site-selective and diastereoselective formation of oxetanes in the PB reaction of 2-furylmethanol derivatives (Scheme 7.27) [45]. However, hydroxy-directed diastereoselectivity was not generalized to face-selectivity in the PB reaction of hydroxy-substituted dihydrofuran and furan derivatives (Scheme 7.28) [46].…”
Section: Stereoselective Syntheses Of Oxetanesmentioning
confidence: 99%
“…This group proposed that hydrogen-bond interactions in the exciplex played an important role in controlling the selectivity. DAuria and coworkers also observed a site-selective and diastereoselective formation of oxetanes in the PB reaction of 2-furylmethanol derivatives (Scheme 7.27) [45]. However, hydroxy-directed diastereoselectivity was not generalized to face-selectivity in the PB reaction of hydroxy-substituted dihydrofuran and furan derivatives (Scheme 7.28) [46].…”
Section: Stereoselective Syntheses Of Oxetanesmentioning
confidence: 99%
“…13 Recently we reported that the reaction between aromatic aldehydes and ketones with 2-furylmethanols give the corresponding adducts in good yields with high regio-, stereo-, and enantioselectivity. 14 We observed that the reaction occurred on the most hindered side of the molecule. This behavior was explained assuming the presence of an electron transfer process (in which the hydroxyl group plays an important role) followed by radical coupling between furyl carbon in α position and the oxygen on the carbonyl group.…”
Section: Methodsmentioning
confidence: 94%
“…Thus, a clear change in the regioselectivity going from 4,4'-dichlorobenzophenone (attack on positions 2,3) to 4,4'-dimethoxybenzophenone (attack on positions 4,5) can be seen, benzophenone showing an intermediate behavior. In our previous work 14 we formulated the hypothesis that the photochemical reaction of 2-furylmethanols with aromatic ketones involves a single electron transfer from the furan derivatives to the ketone followed by radical coupling with the formation of zwitterionic species. In contrast with current opinions in this field, 1 we thought that the most probable structures for these zwitteronic species would be those represented in the Figure. Our point of view can be supported by results of theoretical calculations showing that stability of intermediates explains the regiochemical behavior of the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…While the reaction of 2-furylmethanol with benzophenone showed low regioselectivity, the presence of larger substituents on the carbon bearing the alcoholic function allows a high regioselectivity (Scheme 7) [37]. Furthermore, when 2-furylethanol (20) was used as substrate, a 1 : 1 mixture of stereoisomers was obtained, while, when 1-(2-furyl)-benzylic alcohol (21) was the substrate, only one diastereoisomer was obtained.…”
Section: Photoaddition Of Carbonyl Compounds To Chiral Furansmentioning
confidence: 99%
“…The reaction of 2-furylphenylmethanol gave complete diastereoisomeric control when it reacted with benzophenone [37]. The conformers of this substrate are reported in Figure 16.…”
Section: Photoaddition Of Carbonyl Compounds To Chiral Furansmentioning
confidence: 99%